Pengaruh Implementasi Akuntansi Syariah Terhadap Nilai Perusahaan: Tinjuan Berdasarkan Bagan Akuntansi Syariah Kontemporer - Zulfahmi Zulfahmi; Rayyan Firdaus (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2024)
The implementation of Islamic accounting in the business world has gained increasing attention as awareness grows regarding the financial and operational principles outlined by Islamic law. Islamic accounting, which adheres to the principles of Shariah, aims to ensure that a company's transactions and financial reports comply with Islamic guidelines. This paper aims to analyze the impact of the implementation of Islamic accounting on firm value, with a focus on examining the contemporary Islamic accounting framework, which includes structures and methodologies for more transparent reporting. This research also identifies factors that can strengthen or hinder the adoption of Islamic accounting in improving a company’s financial performance, as well as its impact on investor perceptions. The analysis results indicate that companies consistently applying Islamic accounting principles can enhance investor trust, thereby improving the company's value. Thus, the implementation of Islamic accounting can be an effective strategy to enhance the credibility and competitiveness of a company in a market increasingly focused on ethical and transparent financial practices.